Digital ecclesiology and Africa’s digital natives: prospects and challenges: Prospects and Challenges - Ndereba, K.M. (Acta Theologica, 2023)
The COVID-19 pandemic has raised important issues for the church. Churches have grappled with ministering to their congregants in light of the changes in physical gatherings over the past two years. While the digital mode of ministry has strengthened the church’s missional outreach, churches have struggled with two foundational questions: the nature and the mission of the church. This article engages the emerging research in digital ecclesiology from the lens of reformed ecclesiology –particularly using the ecclesiology of Berkhof and the Westminster Standards as interlocutors – and offers prospects and challenges for the church’s ministry to digital natives in Africa. It argues that digital ecclesiology should not be perceived as a hindrance to the church or be blindly accepted. It should rather be critically engaged to delineate its prospects and challenges for the church’s ministry. More specifically, this article argues that the digital mode of ministry enriches the church’s missional calling as it reaches out to Africa’s digital natives; expands the understanding of church as organism and invisible, and creates specific challenges for the church’s ministry in terms of key concepts such as identity, authority, and community.